Contemporary illustration on music album cover - Khairol Anwar, Adibah Hazwani (Universiti Teknologi MARA, Perak, 2022)
This project is project of redesign photograph music album cover to find out the effectiveness of contemporary illustration on music album cover to promote music. For this project, the album of LiSa, a Japanese singer and songwriter, is chosen because she recently top many music streaming-ranking lists.